1 <span class="kw4">int</span> f<span class="br0">(</span><span class="kw4">int</span> x<span class="br0">)</span>
2 <span class="br0">{</span>
3 <span class="kw1">return</span> x <span class="sy0"><</span> 2 <span class="sy0">?</span> x <span class="sy0">:</span> f<span class="br0">(</span>x <span class="sy0">-</span> 1<span class="br0">)</span> <span class="sy0">+</span> f<span class="br0">(</span>x <span class="sy0">-</span> 2<span class="br0">)</span><span class="sy0">;</span>
4 <span class="br0">}</span>